1997
DOI: 10.1089/aid.1997.13.945
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Immunization Is Superior to Vaginal, Gastric, or Rectal Immunization for the Induction of Systemic and Mucosal Anti-HIV Antibody Responses

Abstract: Vaginal anti-HIV antibody responses may be beneficial, and possibly required, for vaccine-induced protection against HIV infection acquired through receptive vaginal intercourse. We have previously determined that intranasal immunization with a hybrid HIV peptide and cholera toxin induced vaginal anti-HIV IgA responses in BALB/c and C57BL/6 mice. To determine if vaginal, gastric, or rectal boosting would enhance the induction of vaginal anti-HIV IgA responses over those observed with intranasal immunization on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
59
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 33 publications
4
59
0
Order By: Relevance
“…Indeed, our previous studies (7,8) and studies of other groups (9,(33)(34)(35)(36) demonstrated a strong rationale for development of a mucosal AIDS vaccine to generate sufficient mucosal immune responses (both mucosal Ab and CD8 ϩ CTL) to keep the virus under control locally in the gut mucosa and in the systemic circulation as well. We showed that in mice, a mucosal vaccine can be more effective than the same vaccine given s.c. and this protective effect is mediated by mucosal CD8…”
Section: A Novel Functional Ctl Avidity/activity Compartmentalizationmentioning
confidence: 99%
“…Indeed, our previous studies (7,8) and studies of other groups (9,(33)(34)(35)(36) demonstrated a strong rationale for development of a mucosal AIDS vaccine to generate sufficient mucosal immune responses (both mucosal Ab and CD8 ϩ CTL) to keep the virus under control locally in the gut mucosa and in the systemic circulation as well. We showed that in mice, a mucosal vaccine can be more effective than the same vaccine given s.c. and this protective effect is mediated by mucosal CD8…”
Section: A Novel Functional Ctl Avidity/activity Compartmentalizationmentioning
confidence: 99%
“…The nasal route is particularly attractive because of its simplicity and proven efficacy (16)(17)(18). Significant mucosal and systemic responses might be achieved after nasal immunization in primates with an appropriate adjuvant and boosting regimen.…”
mentioning
confidence: 99%
“…If N imm induces both rectal and genital tract mucosal immune responses, it could be a more effective mucosal administration route for STD vaccines, because R imm and V imm , though highly effective for induction of local responses, generate little or no specific IgA at distal mucosal sites (7-9, 29, 30). Studies in mice have also suggested that N imm might be economically advantageous to other mucosal immunization routes because lower Ag doses can generate mucosal Ab responses comparable to those induced by higher doses administered elsewhere (6,31,32). To determine whether this may be the case in humans, we administered 10-fold lower cholera vaccine doses in the nasal cavity of women and compared the magnitude of the mucosal and systemic Ab responses generated to those induced by higher doses in women who received V-FP imm , V-LP imm , or R imm .…”
mentioning
confidence: 99%